Lameness in cattle herd due to lime toxicity: A case report - Abdullah, Faez Firdaus Jesse; Chung, Eric Lim Teik; Sadiq, Muhammad Abubakar; Adamu, Lawan; Haron, Abdul Wahid; Abba, Yusuf; Tijjani, Abdulnasir; Mohammed, Konto; Osman, Abdinasir Yusuf; Lila, Mohd Azmi Mohd (Journal of Advanced Veterinary and Animal Research, 2015)
Forty adult Friesian cows were presented to the University Veterinary Hospital, Universiti Putra Malaysia with primary complain of lameness. Upon physical examination of the cows, open wounds were found at the distal limbs, dorsal hoof, knee joint, metacarpal region, and udder. Based on history, clinical observation and physical examination, the cause of the lameness was diagnosed as of noninfectious origin; the cattle were affected with chemical burn originated from exposure to lime. The affected cattle were treated similarly to that of the line of open wound treatment; the wound was cleaned with topical application of the mixture of dermapred-iodine-benacillin. Flunixin meglumine dosed at 2.2 mg/kg bwt and Oxytetracycline dosed at 20 mg/kg bwt were given intramuscularly as antiinflammatory and prophylactic antibiotic, respectively. This case report describes diagnosis of the cause of lameness, and its management in cattle herd caused by lime toxicity for the first time in Malaysia. http://dx.doi.org/10.5455/javar.2015.b73